Perlindungan Hukum Terhadap Konsumen Dalam Melakukan Transaksi Jual Beli Online - Nelly, Roos (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Shopee is one of the companies that is changing its business processes through e-commerce, which focuses on online buying and selling. Legal protection for consumers in online buying and selling transactions requires confirmation of responsibility related to online buying and selling practices and problems of default caused by business actors. To what extent is the role of the marketplace and business actors responsible for the default losses experienced by consumers. The type of legal research used is empirical juridical legal research. The data sources used are primary data and secondary data. Data collection techniques include interviews, documentation, observation. The data analysis used is qualitative data analysis. The research results obtained by the author are that (1) The buying and selling practices used in the Shopee marketplace use the Business to Consumer and consumer to consumer transaction systems. (2) The responsibility for legal protection for consumers provided by Shopee as a marketplace is related to defaults or unlawful acts caused by business actors, so the burden of responsibility is borne by the business actor by referring to the contract that the parties agreed to. The protection provided by Shopee is limited to supervision, regulator, facilitator, finding solutions, and making decisions regarding defaults or unlawful acts that occur.